ANTIBACTERIAL COATING OF TITANIA-SILICA NANOSOLS ON COTTON FABRICS - , Indriana Kartini , Eko S. Kunarti, Endang T. Wahyuni, Indah Pur ([Yogyakarta] : Chemistry Departement Universitas Gadjah Mada, 2010)
Nanosols of silica (SiO&#8322